Turfgrass‐Applied Metsulfuron‐Methyl Induces Specific Symptomology on Non‐Target Tree Species. Issue 1 (1st June 2019) - Gonçalves, Clebson G.; McElroy, J. Scott; Peppers, J.M.; Basak, Suma; Fain, Glenn B.; Li, Steve
Abstract : Core Ideas: Adventitious leaf and stem dieback can occur from an overapplication of metsulfuron. Label‐rate applications of metsulfuron do not induce injury in trees species. Injury symptoms are not induced by Trimec Classic in trees species.